India Working : - Harriss-White, Barbara (Cambridge University Press, 2003)
Drawing on her knowledge of the country and on theoretical literature, Barbara Harris-White describes the Indian economy through its most important social structures of accumulation. The book explores a range of topics, including labor, class, the state, gender, religious plurality, caste and space. Harris-White's conclusion adeptly challenges the prevailing belief that liberalization releases the economy from political interference.